Pengembangan Instrumen HOTS dalam Pembelajaran Bulutangkis - Hardiansyah, Sefri; Kusmaedi, Nurlan; Ma'mun, Amung; Subarjah, Herman; Syahriadi, Syahriadi (Jurnal Sporta Saintika, 2024)
Higher-Order Thinking Skills (HOTS) are skills that are needed by students in the 21st century. Therefore, lecturers need to develop HOTS through the learning process. However, this effort cannot be carried out optimally because there is no instrument to measure students' HOTS, especially in badminton learning that has met the standards of validity and reliability. The purpose of this research is to develop HOTS instruments in badminton learning. This research is classified as development research (R&D) involving nine validators as assessors and 39 students as test subjects. The instrument consists of three indicators: analyzing, evaluating and creating. Data analysis used Aiken V, ICC, Pearson correlation and Cronbach's alpha. The results stated that 17 HOTS items in badminton learning were valid and reliable.